The method of analysis and synthesis and the discovery of Neptune - Molina Betancur, Sebastián (Estudios de Filosofía, 2017)
The discovery of Neptune was one of the greatest achievements of nineteenth-century astronomy. Using nothing but calculus and some observations of the Uranus’ anomalous motion, Adams and Le Verrier got to determine, independently, the possible place and mass of a hypothetical planet, which would produce its observational discovery. In this paper I will demonstrate that the methods used by these astronomers were influenced by Newton’s method of analysis and synthesis. Considering this, I will also expose, that some astronomy’s general epistemological principles could be deduced when we consider these investigation methods.